Heat conduction issues in laser-induced incandescence - Will, Stefan; et al. (International Bunsen Discussion Meeting and Workshop on Laser-Induced Incandescence: Quantitative Interpretation, Modelling, Application, LII 2005, 2005)
Uncertainties in modelling heat conduction in connection with the application of laser-induced incandescence (LII) to primary particle sizing are discussed. Besides a comparison between commonly used models an experimental study employing specified carbon blacks was performed. An overall good correlation of LII-values and those from electron microscopy has been found. Based on these data an effective accommodation coefficient of α = 0.23 is determined and the influence of aggregate size on primary particle sizing has been quantified.